Tailoring an alien ferredoxin to support native-like P450 monooxygenase activity. - Bell, S; McMillan, J; Yorke, J; Kavanagh, E; Johnson, E; Wong, L (2012)
A ferredoxin associated with biological Fe-S cluster assembly has been remodelled to transfer electrons to a P450 enzyme and support substrate oxidation at 80% of the physiological ferredoxin activity, opening up the possibility of tailoring ferredoxins to reconstitute the activity of P450 enzymes for which the electron transfer partner proteins are not known.